(untitled) (London Journal of Engineering Research, 2024)
The vertical grain sorting is associated with the deposition and transport process’s energy, rate, and duration. In a model where no incoming flux is used, erosion occurs until a static armor layer is formed on the surface of the active layer. A numerical model based on the Günter experiment was built on TELEMAC coupled with SISYPHE to analyze such a phenomenon. Then, the sensitivity of the model’s parameters was analyzed, and the relevant combination of parameters was selected for model calibration. After that, the model was calibrated by using water depth and percentage of shorted grains, and the grain sorting, bed level change, and water level were observed and analyzed at different timesteps. The model result showed that Hunziker’s bed load transport formula, in combination with Strickler’s bed roughness of 61, gave the simulation results closer to the Günters’ measurements. The model also showed that the static armor layer started forming on the surface of the active layer after 12 days with the maximum bed shear stress of 1.98 N/m2. For the reliability analysis of these results, this model’s result should be compared with the results of other models. As an option, the Artificial Neural Network model could be used